Tracheobronchial Stenting is Safe and Effective in Relieving Upper Airway Obstruction - Pang, Yong Kek; Laim, C.K.; Leow, C.H.; Shyamala, P.; Zal, A.R. (Malaysian Medical Association, 2006)
Many studies have shown that tracheobronchial stenting is effective in relieving respiratory distress secondary to major airway obstruction due to lung or oesophageal cancer. A retrospective review on the benefits and complications of self-expandable metallic stent (SEMS) insertion through flexible bronchoscopy for the palliative treatment of upper airway obstruction in University Malaya Medical Centre was performed. Ten patients underwent this procedure. Relief of dyspnoea was immediate following stent insertion in all patients. Stent migration occurred in one patient and three patients had restenosis of the central airway. We conclude that tracheobronchial stenting via flexible bronchoscopy is feasible and safe.